Textile-to-mortar bond behavior: An analytical study - Esfahani, Ali Dalalbashi (2021)
Reliable design and application of textile-reinforced mortar (TRM) composites for the repair of existing masonry and concrete structures requires a fundamental understanding of the textile-to-mortar bond behavior as one of the main mechanisms controlling their nonlinear response and cracking behavior. Suitable test setups and analytical models are needed to extract the bond-slip laws from the experimental pull-out tests. This paper proposes a new bond-slip law and analytical model, which predicts the bond behavior of lime and cement-based TRM composites considering the slip hardening and softening effects observed in experimental tests. For this purpose, the pull-out response of experimental specimens with different fiber types (steel and glass), bond lengths, and mortar age are analyzed, and their bond slip-laws are extracted. The accuracy of the developed model is shown by comparing analytical and experimental results.